2014
DOI: 10.1101/cshperspect.a016394
|View full text |Cite
|
Sign up to set email alerts
|

DNA Degradation and Its Defects

Abstract: DNA is one of the most essential molecules in organisms, containing all the information necessary for organisms to live. It replicates and provides a mechanism for heredity and evolution. Various events cause the degradation of DNA into nucleotides. DNA also has a darker side that has only recently been recognized; DNA that is not properly degraded causes various diseases. In this review, we discuss four deoxyribonucleases that function in the nucleus, cytosol, and lysosomes, and how undigested DNA causes such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 113 publications
0
45
0
Order By: Relevance
“…Enzymatic mechanisms for removal of DNA methylation may release repaired products into the bloodstream and consequently they can appear in the urine. In fact, the deoxynucleosides of 5mC and 5hmC –namely 5-methyl-2-deoxycytidine (5mdC) and 5-hydroxymethyl-2-deoxycytidine (5hmdC)– have recently been detected and quantified in urine3536, and several biological processes such as apoptosis can degrade DNA into single deoxynucleosides37. According to these studies, urinary 5mdC and 5hmdC contents may offer a view of the metabolic and functional status of tissues or organs in the human body.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymatic mechanisms for removal of DNA methylation may release repaired products into the bloodstream and consequently they can appear in the urine. In fact, the deoxynucleosides of 5mC and 5hmC –namely 5-methyl-2-deoxycytidine (5mdC) and 5-hydroxymethyl-2-deoxycytidine (5hmdC)– have recently been detected and quantified in urine3536, and several biological processes such as apoptosis can degrade DNA into single deoxynucleosides37. According to these studies, urinary 5mdC and 5hmdC contents may offer a view of the metabolic and functional status of tissues or organs in the human body.…”
Section: Resultsmentioning
confidence: 99%
“…The biological mechanism for the interference of phthalates with urinary 5mdC and 5hmdC is unclear. Urinary 5mdC and 5hmdC may be the degradation products of genomic DNA metabolism (e.g., DNA degradation, DNA excise repair), which could be affected by several processes such as apoptosis or DNA damage (Kawane et al, 2014;Nagata et al, 2003). Previous research showed that phthalate exposure increased the production of reactive oxygen species (Rusyn et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several biological processes, such as apoptosis, can cause DNA to degrade into single deoxynucleosides (Kawane et al, 2014;Nagata et al, 2003). It is hypothesized that urinary 5mdC and 5hmdC molecules may result from metabolism of methylated DNA (e.g., DNA degradation or DNA excision repair) (Hu et al, 2012;Yin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…4B). G4DNA structures from damaged G-rich sequences provide a direct mechanism for the cell to sense oxidative stress-induced DNA damage (56). The formation of stress granules is known to modulate RNA translation during oxidative stress (24,57).…”
Section: Discussionmentioning
confidence: 99%